Anti-Inflammatory Effects of GLP-1-Based Therapies beyond Glucose Control - Young-Sun Lee; Hee-Sook Jun (Mediators of Inflammation)
Glucagon-like peptide-1 (GLP-1) is an incretin hormone mainly secreted from intestinal L cells in response to nutrient ingestion. GLP-1 has beneficial effects for glucose homeostasis by stimulating insulin secretion from pancreatic beta-cells, delaying gastric emptying, decreasing plasma glucagon, reducing food intake, and stimulating glucose disposal. Therefore, GLP-1-based therapies such as GLP-1 receptor agonists and inhibitors of dipeptidyl peptidase-4, which is a GLP-1 inactivating enzyme, have been developed for treatment of type 2 diabetes. In addition to glucose-lowering effects, emerging data suggests that GLP-1-based therapies also show anti-inflammatory effects in chronic inflammatory diseases including type 1 and 2 diabetes, atherosclerosis, neurodegenerative disorders, nonalcoholic steatohepatitis, diabetic nephropathy, asthma, and psoriasis. This review outlines the anti-inflammatory actions of GLP-1-based therapies on diseases associated with chronic inflammation in vivo and in vitro, and their molecular mechanisms of anti-inflammatory action.